Ion Exchange Kinetics of Pb2+, Cu2+, Cd2+ and Mn2+ Ions on Thermally Stable Bimetallic Ion Exchange Material: TitaniumTin Tungstate - Dhanitha M.A.; Nimisha K.V.; Janardanan C. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Heavy metal contamination in the environment has been of great concern because of their increased discharge, toxic nature and other adverse effects on the receiving streams. Titaniumtin tungstate (TSW), an efficient bimetallic ion exchange material was synthesized by co-precipitation method and is used to study the ion exchange kinetics of some toxic heavy metal ions. The exchanger was characterized by some physicochemical properties like FTIR, XRD, TGA-DTA, SEM and ion exchange properties to validate the structure and ion exchange behavior. The exchanger shows high ion exchange capacity of 1.2 meqg−1 as well as good chemical and thermal stability. Explicit Nernst-Plank approximation is applied to study the reaction kinetics for four heavy metal ions (Pb2+, Cu2+, Cd2+ and Mn2+) on the surface of TSW. The kinetic studies carried out under particle diffusion controlled phenomenon. On the basis of kinetic studies, various physical parameters like fractional attainment of equilibrium U(τ), self diffusion coefficients (D0), energy of activation (Ea) and entropy of activation (∆S*) were estimated to evaluate the mechanism of ion exchange and indicated that the ion exchange process is feasible and spontaneous.